Dietary Polyphenols and Their Role in Oxidative Stress-Induced Human Diseases: Insights Into Protective Effects, Antioxidant Potentials and Mechanism(s) of Action - Rudrapal, Mithun; Khairnar, Shubham J.; Khan, Johra; Dukhyil, Abdulaziz Bin; Ansari, Mohammad Azam; Alomary, Mohammad N.; Alshabrmi, Fahad M.; Palai, Santwana; Deb, Prashanta Kumar; Devi, Rajlakshmi (Frontiers in Pharmacology, 2022)
Dietary polyphenols including phenolic acids, flavonoids, catechins, tannins, lignans, stilbenes, and anthocyanidins are widely found in grains, cereals, pulses, vegetables, spices, fruits, chocolates, and beverages like fruit juices, tea, coffee and wine. In recent years, dietary polyphenols have gained significant interest among researchers due to their potential chemopreventive/ protective functions in the maintenance of human health and diseases. It is believed that dietary polyphenols/ flavonoids exert powerful antioxidant action for protection against reactive oxygen species (ROS)/ cellular oxidative stress (OS) towards the prevention of OS-related pathological conditions or diseases. Pre-clinical and clinical evidences strongly suggest that long term consumption of diets rich in polyphenols offer protection against the development of various chronic diseases such as neurodegenerative diseases, cardiovascular diseases (CVDs), cancer, diabetes, inflammatory disorders and infectious illness. Increased intake of foods containing polyphenols (for example, quercetin, epigallocatechin-3-gallate, resveratrol, cyanidin etc.) has been claimed to reduce the extent of a majority of chronic oxidative cellular damage, DNA damage, tissue inflammations, viral/ bacterial infections, and neurodegenerative diseases. It has been suggested that the antioxidant activity of dietary polyphenols plays a pivotal role in the prevention of OS-induced human diseases. In this narrative review, the biological/ pharmacological significance of dietary polyphenols in the prevention of and/or protection against OS-induced major human diseases such as cancers, neurodegenerative diseases, CVDs, diabetes mellitus, cancer, inflammatory disorders and infectious diseases have been delineated. This review specifically focuses a current understanding on the dietary sources of polyphenols and their protective effects including mechanisms of action against various major human diseases.